Qualitative exploration of stakeholders' perspectives of involuntary admission under the Mental Health Act 2001 in Ireland. (27th October 2016) - Smyth, Siobhán; Casey, Dympna; Cooney, Adeline; Higgins, Agnes; McGuinness, David; Bainbridge, Emma; Keys, Mary; Georgieva, Irina; Brosnan, Liz; Beecher, Claire; Hallahan, Brian; McDonald, Colm; et al.
Abstract: There is international interest in, and continued concern about, the potential long‐term impact of involuntary admission to psychiatric institutions, and the effect this coercive action has on a person's well‐being and human rights. Involuntary detention in hospital remains a controversial process that involves stakeholders with competing concerns and who often describe negative experiences of the process, which can have long‐lasting effects on the therapeutic relationship with service users. The aim of the present study was to explore the perspectives of key stakeholders involved in the involuntary admission and detention of people under the Mental Health Act 2001 in Ireland. Focus groups were used to collect data. Stakeholders interviewed were service users, relatives, general practitioners, psychiatrists, mental health nurses, solicitors, tribunal members, and police. Data were analysed using a general inductive approach. Three key categories emerged: (i) getting help; (ii) detention under the Act; and (iii) experiences of the tribunal process. This research highlights gaps in information and uncertainty about the involuntary admission process for stakeholders, but particularly for service users who are most affected by inadequate processes and supports. Mental health law has traditionally focussed on narrower areas of detention and treatment, but human rights law requires a greater refocussing on supporting service users to ensure a truly voluntary approach to care. The recent human rights treaty, the UN Convention on the Rights of Persons with Disabilities, is to guarantee a broad range of fundamental rights, such as liberty and integrity, which can be affected by coercive processes of involuntary admission and treatment.